2015
DOI: 10.1007/s00415-015-7969-z
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of MELAS main mutation in a phenotype-targeted young ischemic stroke patient population

Abstract: Mitochondrial diseases, predominantly mitochondrial encephalomyopathy, lactic acidosis, and strokelike episodes (MELAS), may occasionally underlie or coincide with ischemic stroke (IS) in young and middleaged individuals. We searched for undiagnosed patients with MELAS in a target subpopulation of unselected young IS patients enrolled in the Stroke in Young Fabry Patients study (sifap1). Among the 3291 IS patients aged 18-55 years recruited to the sifap1 study at 47 centers across 14 European countries, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…During follow‐up, five (27.8%) MELAS‐mtND patients died of generalized seizures. Short stature in this study was defined as male ≤ 165 cm and female ≤ 155 cm 24 at age > 16 years old. Three (3/13, 23.1%) MELAS‐mtND patients exhibited short stature.…”
Section: Resultsmentioning
confidence: 99%
“…During follow‐up, five (27.8%) MELAS‐mtND patients died of generalized seizures. Short stature in this study was defined as male ≤ 165 cm and female ≤ 155 cm 24 at age > 16 years old. Three (3/13, 23.1%) MELAS‐mtND patients exhibited short stature.…”
Section: Resultsmentioning
confidence: 99%
“…32 Having a "genetically" pathogenic variant of a monogenic disorder does not necessarily mean that a patient has corresponding clinical or imaging characteristics because of high variability of the penetrance and expressivity. Previous studies also reported that clinical and/or brain MR findings were not enough to specify diagnosis of monogenic disorders such as Fabry disease, 33 MELAS (mitochondrial encephalomyopathy, lactic acidosis, and strokelike episodes), 34 and CADASIL. 35 For patients with CRGVs but no typical features of the corresponding disorders at stroke onset, we could not determine whether they would develop those features ultimately and how long it would take.…”
Section: Discussionmentioning
confidence: 99%
“…There are data to suggest this may be an underestimate due to lack of recognition to screen for monogenetic causes. Some studies estimate the incidence in young stroke patients could be up to 7% (144,145). To be clear, these are not "stroke genes;" rather, they are genetic conditions in which stroke is a presenting feature.…”
Section: Monogenetic Stroke Disordersmentioning
confidence: 99%